2005
DOI: 10.1002/pon.873
|View full text |Cite
|
Sign up to set email alerts
|

Depression experienced by young women newly diagnosed with breast cancer

Abstract: Breast cancer is the most common type of cancer among women. While almost a quarter of women diagnosed with breast cancer are 50 or younger, few studies are focused on them. Compared to older women, young women have more difficulty adjusting to the breast cancer diagnosis, report more symptoms of distress and a lower quality of life. This study examined depressive symptoms among an ethnically diverse sample of 331 young women, newly diagnosed with breast cancer. The focus was to determine the relative importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
101
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 42 publications
12
101
1
9
Order By: Relevance
“…As in other studies, there was no statistically significant association of cancer-specific variables with depression, 12,[15][16][17][18][19]21 indicating that these variables alone did not have an influence on depression. The only variable with a trend toward statistical significance was a family history of depression ( p = 0.059 ) and it is known that major depressive disorder is 1.5 to 3 times more common among first-degree biological relatives of people with this disorder than among the general population.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…As in other studies, there was no statistically significant association of cancer-specific variables with depression, 12,[15][16][17][18][19]21 indicating that these variables alone did not have an influence on depression. The only variable with a trend toward statistical significance was a family history of depression ( p = 0.059 ) and it is known that major depressive disorder is 1.5 to 3 times more common among first-degree biological relatives of people with this disorder than among the general population.…”
Section: Discussionsupporting
confidence: 65%
“…It is assumed that functional, everyday stress and other disorders unrelated to cancer cause major influence on the patient's psychological function, due to factors inherent in the premorbid personality. 16 Contextual variables, rather than risk factors directly related to cancer, appear to be predictive factors for the onset of depression in breast cancer patients 12,[15][16][17] , among which stand out the structure of personality and problem-coping ability. 6 The majority of our sample consisted of women older than 49 years old, white, married, of low education, low income, no family history of breast cancer and / or depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological trauma that starts with cancer diagnosis lasts longer, and increases during the chemotherapy period, which requires multiple hospital stays. Previous studies have shown that 29-47% of cancer patients have a psychological disorder that can be diagnosed (Atesci et al, 2003;Wong-Kim and Bloom, 2005;Friedman et al, 2006;Ozkan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of features such as: emotional control; low neuroticism, associated with Type C personality; the use of ineffective coping strategies; and low perceived social support (from partner, family, friends and health professionals), may negatively influence the way women react to the disease process [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%